MODELING OF MICROSTRIP ANTENNA ARRAYS USING THE INTEGRAL EQUATION METHOD - А. V. Ulanouski; V. V. Kizimenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The application of the method of integral equations for finding the characteristics and parameters of microstrip antenna arrays is described. When modeling an array of microstrip dipoles each radiator is replaced a wire. The dielectric substrate is taking into account by an introduction of the effective permittivity to the integral equation. From the obtained current distribution it is determined the microstrip dipoles input impedance, taking into account the interaction with the neighboring elements, and calculated radiation pattern of the array and its directivity. The simulation results are compared with the results described in the literature and calculated in the current electrodynamic simulation packages CST MWS, AWR MWO and FEKO.